Analysis of the Proximity Between Perpretator and Victims of Sexual Violence in Forensic Patients’ Clinic at Dr. Soeradji Tirtonegoro Hospital, Klaten, Indonesia: A Cross-Sectional Study from 2019-2021 - Mahila, Niufti Ayu Dewi; T.A, Martiana Suciningtyas; Gizela, Beta Ahlam (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 2 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i02.p05, 2022)
Background: Violence against women and children is a global problem with a serious impact because it causes a decrease in the quality of health both physically and psychologically for victims. Only some reported sexual violence due to fear and negative stigma in society. Klaten is among the highest cases of violence in Central Java from January-March 2021. The purpose of this study is to determine the level and close relationship between perpretrators and victims of sexual violence. Method: A cross-sectional study was conducted using accidental sampling methods from medical record data and Visum et Repertum of sexual violence at Dr. Soeradji Tirtonegoro Hospital, Klaten from January 2019 – December 202. Results: There were 60 cases of sexual violence, the majority aged <18 years amounted to 57 cases (95%), then 18-65 years 3 cases (5%), the majority of victims were women totaling 55 cases (91.66%) and men 5 cases (8.33%). There is no significant correlation between the relationship from perpetrator and the victim on acts of sexual violence, with a very weak correlation strength and the direction of the correlation being in the same direction. Conclusions: Although the results of this study show a weak correlation between the proximity of perpetrators and victims of sexual violence, the risk of sexual violence can occur to anyone regardless of gender and perpetrators can come from anywhere.